Integrated Care Plan In The Hospital Setting: A Scoping Review - Ardi, Bangun Mukti; Nursalam, Nursalam; Rosyid, Alfian Nur (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2023)
Improving the quality of healthcare services in hospitals is one of the main goals of achieving a high-quality healthcare system. One of the efforts to enhance the quality of healthcare services in hospitals is implementing an integrated care plan. This study aims to determine the implementation of integrated care plans in hospitals. There were no limitations on methodologies, dates, or settings when reviewing papers describing qualitative or quantitative studies examining the implementation of integrated care plans in hospitals. The setting, design, and findings were all extracted from key study aspects. The major components of the integrated care plan's key components served as a framework for organizing the findings. There are 15 relevant papers published between 2018 and 2023. Most of the studies reported are qualitative, where healthcare workers reflect on their experiences and preferences regarding implementing an integrated care plan. These studies reported on issues underlying the need for the implementation of an integrated care plan, including poor administrative and management systems, lack of access, lack of coordination, lack of regulation, lack of knowledge, and lack of experience, with the ultimate goal of care being aware of cooperation and benefits for patients. An efficient way to raise patient satisfaction and improve the standard of healthcare services is to establish an Integrated Care Plan in hospitals. The efficacy and efficiency of patient care in hospitals can be improved by implementing a more structured and measurable care plan. Keywords: Integrated care plan, integrated health care systems, integrated delivery system, hospital.